A dual strategy to improve psychotic patients’ compliance using sustained release quetiapine oral disintegrating tablets - Refaat Ahmed; Sokar Magda; Ismail Fatma; Boraei Nabila (Acta Pharmaceutica)
Quetiapine (QT) is a short acting atypical antipsychotic drug effective in schizophrenia and bipolar disorder. This study aims at designing a novel dosage form of sustained release taste-masked QT orally disintegrating tablets (ODTs) based on solid lipid micro-pellets (SLMPs). QT SLMPs were prepared using the hot melt extrusion technique and utilizing three lipid carriers: Compritol, Precirol and white beeswax either alone or in mixtures. They showed sustained QT release and a taste masking effect. The selected QT SLMP was further blended with an aqueous solution containing polyvinylpyrollidone (2.5 %), croscarmellose sodium (2 %) and mannitol (50 %); it was then lyophilized into ODT in a mass ratio of 1:2, respectively. ODTs containing QT SLMPs showed: average wetting time (40.92 s), average oral disintegration time (21.49 s), average hardness (16.85 N) and also imparted suitable viscosity to suspend pellets during the lyophilization process. In conclusion, lyophilization is a promising technique for the formulation of multiparticulate systems into ODTs.